Droits, devoirs et politiques de l'inspecteur général des institutions financières en rapport avec l'administration de la Partie 1A de la Loi sur les compagnies - Gaudry, Hubert (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1985)
The Inspector General is not obliged to refuse documents that are filed and are not consistent with the law. When statutes are filed by the Inspector General, the search for the proposed corporate name is an accessory act that does not imply any obligation on his part, except that he cannot accept a name that has been reserved by another person. The reservation does not give a universal and exclusive right to its owner : it cannot be invoked against unincorporated enterprises. It cannot either be invoked against federal companies just as federal reservations cannot be invoked against provincial companies. Moreover, the Inspector General may refuse a reserved corporate name when the statutes are filed if it has been formerly taken by an unincorporated or federal company. The errors in the statutes that are not imputable to the Inspector General cannot be corrected with retroactive effect.